Evaluating the controlled reopening of nightlife during the COVID-19 pandemic: a matched cohort study in Sitges, Spain, in May 2021 (Reobrim Sitges). Issue 6 (1st June 2022) - Cunillera Puértolas, Oriol; Contreras-Martos, Sara; Marzo-Castillejo, Mercè; López Gallegos, Darío; Acedo Anta, Mateo; Almeda Ortega, Jesús; Colom, Joan; Basora, Josep; Salvador-Gonzalez, Betlem
Abstract : Objectives: To assess the impact of relaxing the state of alarm restrictions on SARS-CoV-2 infections at 14 days among people attending reopened nightclub venues. Design: Matched cohort study with a paired control group (1:5 ratio). Setting: Five small nightclubs with indoor areas and outdoor terraces, in a nightlife-restricted area in Sitges, Spain, on 20 May 2021. Wearing masks was mandatory, drinking was allowed and social distance was not required. Participants: Volunteers were selected through a convenience sampling. To attend the event, participants were required to be older than 17 years, with a negative rapid antigen diagnostic test (Ag-RDT) on the same afternoon, without a positive reverse-transcription PCR (RT-PCR) or Ag-RDT and/or symptoms associated with COVID-19 in the previous 7 days, to not having knowingly been in close contact with someone infected in the previous 10 days and to not have knowingly had close contact with someone with a suspicion of COVID-19 in the previous 48 hours. A control group was paired by exact age, gender, residence municipality, socioeconomic index, previous SARS-CoV-2-confirmed infection and vaccination status, in a 1:5 ratio, from the primary care electronic health records. Primary outcome: Evidence of infection at electronic health records by SARS-CoV-2 at 14-day follow-up. Results: Among the 391 participants (median age 37 years; 44% (n=173) women), no positive SARS-CoV-2 cases were detected at 14 days, resulting in a cumulative incidence estimation of 0 (95% CI 0 to 943) per 100 000 inhabitants. In the control group, two cases with RT-PCR test were identified, resulting in a cumulative incidence of 102.30 (12.4 to 369) per 100 000 inhabitants. Conclusions: Nightlife attendance under controlled conditions and with a requirement for a negative Ag-RDT was not associated with increased transmissibility of SARS-CoV-2 in a pandemic context of low infection rates. In such circumstances, secure opening of the nightlife sector was possible, under reduced capacity and controlled access by Ag-RDT, and environments where compliance with sanitary measures are maintainable.